Development of a Digital Assessment Model for Automated Short Essay Scoring in Islamic Education Study Program - Susilawati, Evi; Siregar, Epi Supriani; Ekalestari, Susi; Harahap, Evi Syuriani (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
Advances in digital technology have driven the transformation of assessment systems in education, including in the Islamic Education Study Program at the Universitas Islam Sumatera Utara. The manual essay assessment process is often considered inefficient, time-consuming, and prone to subjectivity on the part of assessors. This study aims to develop a Digital Automated Short Essay Scoring Assessment Model designed to enhance the effectiveness, speed, and objectivity of essay assessment for students. This study employs a research and development approach with a four-stage model, namely the definition stage, design stage, development stage, and dissemination stage, with a focus on the first three stages. Research data were collected through interviews, observations, document reviews, digital-based essay tests, and user satisfaction questionnaires. Data analysis was conducted using qualitative and quantitative descriptive approaches. The results of the study indicate that the Automated Short Essay Scoring Digital Assessment Model is valid according to experts, feasible for use, and capable of improving the efficiency of the assessment process and student motivation. This model has positive implications by supporting adaptive learning, facilitating instructors in providing quick, accurate, and structured feedback, and encouraging improved quality of academic interaction between instructors and students.